DRIVERS OF GDP GROWTH: EVIDENCE FROM SELECTED EUROPEAN COUNTRIES - Ješić, Milutin (Economic Annals, 2023)
This empirical study analyses the potential determinants of GDP growth in selected European countries using data for 19 countries from Central, Eastern, and South-Eastern Europe for the period 2014 to 2020. The influence of possible drivers of economic growth are investigated by employing dynamic panel data modelling, specifically the system GMM method. The study’s findings reveal that fiscal responsibility, initial development, the inflation rate, and EU membership are the main GDP growth drivers. In addition, we control for the institutional determinants of economic growth and the role of R&D. These results provide further support for the hypothesis that macroeconomic policies conducted in a responsible and sustainable way can significantly improve countries’ growth perspectives. These findings may help us to understand that the trinity of policies, institutions, and technology is a conditio sine qua non of economic growth.